Factors influencing saving habit among residents in Kota Bharu, Kelantan / Anis Alma' Muhamad - Muhamad, Anis Alma' (Faculty of Business and Management, 2019)
The researcher's interest in exploring factors influencing saving habits has greatly increased in recent years due to society's awareness of its importance. Saving habit is an important element in disciplining people to achieve a quality life because peoples who have saving habit will influence the way they manage money throughout their lives. This study seeks to examine the saving habit among residents of Kota Bharu, Kelantan. This study uses primary data by questionnaires and the sample consisted of 200 peoples and the target population of the study is from Kota Bharu's residents. This study uses a Convenience sampling method to collect the data and the results were compiled by using Statistical Package for Society Science (SPSS) software version 22. The result comprised reliability and multiple linear regression analysis. There are four independent variables for this study which are financial literacy, parental socialization, peer influence, and self-control while the dependent variable is the saving habits. From the study, the researcher had gained significant results for all the independent variables.